2012
DOI: 10.1177/0044118x12448801
|View full text |Cite
|
Sign up to set email alerts
|

The Social Network

Abstract: This article looks at the means through which homeless young women are able to improve their flow of social capital by attaining a sense of belonging and forming positive attachments to supportive people and places. In so doing, they also develop relationships with health and social services and improve their overall physical and mental health through stable and supportive interactions. In working with homeless youth, however, the very concept of social capital must be adapted to appropriately respond both to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Young homeless people, for example, with experience of the care system may have had multiple service providers and key workers within a short period of time. Practitioners may provide supportive relationships to people who are homeless in the absence of family (Oliver and Cheff, 2014). However, tensions also exist where practitioners are required to enforce rules and provide support (McGrath and Pistrang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Young homeless people, for example, with experience of the care system may have had multiple service providers and key workers within a short period of time. Practitioners may provide supportive relationships to people who are homeless in the absence of family (Oliver and Cheff, 2014). However, tensions also exist where practitioners are required to enforce rules and provide support (McGrath and Pistrang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…This goes to show that one of the important areas where women marital status becomes an issue and intervenes against them is in urban private accommodation market. Hence, the study of single women and housing access has been on the research agenda of scholars in Western nations for quite awhile (Oliver and Cheff, 2014;Byrne, 2008;Jill and Margaret, 2003;Ross, 1995). For instance, in a study of one-parent family in Tasmania, Australia, Lee (1977) found the position of single mother to be unequivocal both in terms of their ability to compete with other social groups for accommodation, and in control over their housing circumstances exercised by a gatekeeper group.…”
Section: \~Imentioning
confidence: 99%
“…Research on emerging adults and grandparents has suggested that youth have fairly strong feelings of closeness and, to a lesser extent, similarity with their grandparents, particularly maternal grandparents (Mills et al, 2001 ). Oliver and Cheff ( 2014 ) found that grandparents were significant sources of logistical and emotional support even for homeless young women who had difficult relationships with their parents and immediate family members. More recently, research has shown that grandparents can play an important role in mentoring their emerging adult grandchildren, positively impacting identity synthesis (Michałek-Kwiecień, 2022 ).…”
Section: Introductionmentioning
confidence: 99%